Adaptation strategy of karst forests: Evidence from the community‐weighted mean of plant functional traits. Issue 3 (1st March 2022) - Liu, Libin; Hu, Jing; Chen, Xinyao; Xu, Xin; Yang, Yong; Ni, Jian
Abstract: Conservative survival strategy of plants growing in harsh karst habitats is observed from the view of plant functional traits, such as morphological traits and ecological stoichiometry. However, whether the plant communities in karst forests with high species turnover adopt a conservative strategy remains undetermined. This study comprehensively investigated the characteristics of functional traits of dominant plant species in four forests (i.e. Platycarya strobilacea, Quercus fabri, Quercus variabilis, and Pinus massoniana forests) in a trough‐valley karst watershed in Northern Guizhou Province, Southwestern China to explore the adaptation strategy of karst forests at the community level. At the organ and the species levels, traits differed among species, and the leaf and the bark morphological traits and root C:N:P ecological stoichiometry presented large interspecific variations. At the community level, the P . massoniana forest presented the lowest specific root length and dry matter content and tissue density of roots, branch, twig, and bark; the Q . fabri and the Q . variabilis forests displayed low specific leaf area and high dry matter content and tissue density of roots, branch, and twig; and the Platycarya strobilacea forest exhibited high specific leaf area. The P . massoniana forest was subjected to N and P colimitation, and the three other broad‐leaved forests were limited by P supply. The community‐weighted means rather than the arithmetic means of traits were preferential to represent the trait characteristics at the community level. From the view of plant functional traits at the community level, karst forests develop multiple functional traits like low specific leaf area, high dry matter content and tissue density of leaf, roots, branch, and twig, and decrease N and P investments in leaf for a conservative survival strategy to adapt to harsh habitats. Abstract : This manuscript is about the comprehensive investigation of 18 morphological traits of leaf, root, branch, twig, and bark and C:N:P ecological stoichiometry of leaf, root, and branch of dominant species in four karst forests (i.e., Platycarya strobilacea, Quercus fabri, Quercus variabilis, and Pinus massoniana forests) in a trough‐valley karst terrain in Northern Guizhou Province, Southwestern China. Results show that the community‐weighted means rather than the arithmetic means of traits were preferential to represent the trait characteristics at the community level. From the view of plant functional traits at the community level, karst forests develop multiple functional traits like low specific leaf area, high dry matter content and tissue density of leaf, roots, branch, and twig, and decrease N and P investments in leaf for a conservative survival strategy to adapt to harsh habitats.